2003
DOI: 10.1073/pnas.262672599
|View full text |Cite
|
Sign up to set email alerts
|

Extensive and specific responses of a eukaryote to bacterial quorum-sensing signals

Abstract: Many bacteria use N-acyl homoserine lactone (AHL) signals to coordinate the behavior of individual cells in a local population. The successful infection of eukaryotic hosts by bacteria seems to depend particularly on such AHL-mediated ''quorum-sensing'' regulation. We have used proteome analysis to show that a eukaryotic host, the model legume Medicago truncatula, is able to detect nanomolar to micromolar concentrations of bacterial AHLs from both symbiotic (Sinorhizobium meliloti) and pathogenic (Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
352
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 465 publications
(366 citation statements)
references
References 26 publications
(30 reference statements)
6
352
0
8
Order By: Relevance
“…Roots of the model host plant Medicago truncatula (legume), used to study symbiotic relationships with Sinorhizobium meliloti and pathogenic relationships with P. aeruginosa, were treated with nanomolar concentrations of AHLs, and subsequent changes in the plant proteome were measured (263). Cellular levels of at least 154 proteins were found to significantly change in the presence of AHLs, with concentrations of some increasing and those of others decreasing.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots of the model host plant Medicago truncatula (legume), used to study symbiotic relationships with Sinorhizobium meliloti and pathogenic relationships with P. aeruginosa, were treated with nanomolar concentrations of AHLs, and subsequent changes in the plant proteome were measured (263). Cellular levels of at least 154 proteins were found to significantly change in the presence of AHLs, with concentrations of some increasing and those of others decreasing.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…Cellular levels of at least 154 proteins were found to significantly change in the presence of AHLs, with concentrations of some increasing and those of others decreasing. Astonishingly, the response to AHL treatments included secretions by the root tissues that contained compounds having QS agonist properties that were able to induce a LasR reporter, as well as QS-inhibiting properties that were able to block an AI-2-based reporter (263). Though studies have yet to identify the compounds produced by the plant roots, the work offers a glimpse of the complex interplay between plants and microbes, whether their relationships are symbiotic or pathogenic.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…Recently, more evidence demonstrate that AHLs are able to modulate plant growth and development (Mathesius et al, 2003;Ortíz-Castro et al, 2008;von Rad et al, 2008;Méndez-Bravo et al, 2010;MorquechoContreras et al, 2010). In Arabidopsis, treatment with AHLs alters primary growth, lateral root formation, and root hair development; specifically, AHLs with different lengths of unmodified branched chains differentially affect the root architecture.…”
Section: -O-c10-hl Promotes Polar Auxin Transportmentioning
confidence: 99%
“…For example, C10-HL treatment was unable to enhance GUS activity in Arabidopsis transgenic seedlings harboring the auxinresponse DR5:uidA gene construct (Ortíz-Castro et al, 2008). However, Mathesius et al (2003) reported that AHLs with an acyl-substituted branched chain, such as 3-O-C12-HL and 3-O-C16-HL, induce the tissue-specific activation of the auxin-response GH3 and the chalcone synthase genes in the model legume M. truncatula; these findings imply that there is some level of variability in auxin signaling in response to AHLs. To confirm this, we measured the abilities of various AHLs to activate polar auxin transport .We found that the AHLs with an acyl-modified branched chain at the C3 position, such as 3-O-C10-HL, 3-O-C8-HL, and 3-O-C12-HL, could efficiently promote polar auxin transport, with 3-O-C10-HL showing the greatest response (Fig.…”
Section: Branched Chain Structures Of Ahls Affect Root Auxin Polar Trmentioning
confidence: 99%
See 1 more Smart Citation